PENGARUH PENERAPAN SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA INDIVIDUAL DENGAN BUDAYA ORGANISASI SEBAGAI PEMODERASI - Wiguna, Dewa Made Agung Putra; Dharmadiaksa, Ida Bagus (E-Jurnal Akuntansi, 2016)
Implementation of information systems in the organization will affect the performance of individuals within the organization. This study aimed to examine the effect of the application of accounting information system of individual performance and to determine the moderating influence of organizational culture in the application of accounting information system of individual performance in the savings and credit cooperatives in the district of Tabanan. This research was conducted at 24 savings and credit cooperatives in the district of Tabanan. Sample selection is done by using purposive sampling method. Data collected through questionnaires. The analysis technique used in this study are moderated regession analysis. The study found that the application of the accounting information system with positive impact on the performance of individual, strengthens organizational culture influence the application of accounting information systems on individual performance.
Keywords: Individual Performance, Application of Accounting Information Systems, Organizational Culture